Employers’ perception towards technical, vocational, educational and training (TVET) graduates / Abdul Amir Asraf Abdul Latif - Abdul Amir Asraf, Abdul Latif (2018)
Malaysia has provided many institutions that produce skilled local labor through TVET program initiative launch by the Malaysian government, but still TVET graduates not been given priority by the employers. TVET students have been produce but still not meeting employer requirement to work in construction industries. Even though technical institution in Malaysia has produced a substantial number of technical graduate for skilled labour, but construction industries still claimed that there is a shortage of local skilled labour to fulfil the vacancies to work in a construction site. Thus, the aim of this research is to identify the perception of employers towards TVET graduates in Malaysia. The objective of this research to determine the participant of TVET graduates working in the construction site, and to identify the perception of employers towards TVET graduates. Review of literature was conducted and a questionnaire survey was used to obtain the information needed to meet the requirements of this inquiry. The questionnaire was distributed to 120 respondents and 90 respondents are responding to the survey. The distribution was involved registered contractor Grade 7 under CIDB Perak State. The data were analyzed by using the SPSS software with Average Index. The result from the analysis shows that low participation TVET graduates working in construction industries due to less hiring of TVET graduates from the employer despite TVET institution have produced a huge number of graduates. The employers give positive perception towards TVET graduates and satisfy with the overall performance of TVET graduates work in the construction industries. The findings of this study, hopefully, will be used as a guidance to raise the involvement of TVET graduates in the construction site.